Threshold Anomaly Phenomenon of Optical Model Potentials for 7Li+207Pb System at Energies Near Coulomb Barrier - HUANG Zhijie1, LIN Chengjian1, 2, , YANG Lei1, , JIA Huiming1, MA Nanru1, WEN Peiwei1, YANG Feng1, WANG Danying1, LUO Tianpeng1, CHANG Chang1, DUAN Hairui1, ZHU Songxian1, YIN Cheng1, YANG Jionghe1, 2, WANG Haorui1, FAN Zerui1, FU Lingyi1, LI Huiyan1 (Yuanzineng kexue jishu)
The nuclear interaction serves as a fundamental component in the investigation of the mechanisms underlying nuclear reactions. The optical model potential (OMP) is extensively employed to phenomenologically describe the interaction of nuclear collisions. It is well established that the OMPs are closely linked to the internal structures of the nuclei involved in the collision. Consequently, it follows that OMPs for weakly-bound systems will differ significantly from those of tightly-bound systems, a fact that has generated considerable interest in current research. For tightly bound nuclear systems, OMPs exhibit a threshold anomaly （TA） phenomenon in the energy region near the Coulomb barrier, where the connection between the real and imaginary potentials is well described by the dispersion relation. For weakly bound nuclei (such as 6Li and 9Be) induced reactions, OMPs show an abnormal “threshold anomaly” phenomenon, where the connection between the real and imaginary potentials is well described by the dispersion relation. However, the behavior of OMPs remains controversial for the weakly bound nucleus 7Li induced reactions. Therefore, this study is focused on the 7Li+207Pb system, aiming to measure and analyze its phenomenological OMP with precision. The experiment was carried out on the R60 nuclear reaction terminal of the HI-13 tandem accelerator located at the China Institute of Atomic Energy. In the present work, elastic scattering angular distributions of the 7Li+207Pb system have been measured with high precision at energies near and well below the Coulomb barrier. Through fitting the angle distributions of elastic scattering by the optical model, the OMP parameters of the 7Li system were successfully determined. Although 7Li was commonly considered as a weakly bound nucleus with a low breakup threshold, its OMP exhibits the typical threshold anomaly phenomenon: The real potential presents a bell-like shape around the barrier, and the imaginary potential decreases below the barrier and then falls quickly down to 0. In addition, experimental results show the dispersion relation is not applicable for this system, which may be a common phenomenon for exotic nuclear systems. Moreover, the reaction threshold of the 7Li+207Pb system is determined from the data in the deep sub-barrier energy region, about 0.82VB (the height of the Coulomb barrier), which is between the 0.93VB of the typical tightly bound 16O+208Pb system and the 0.73VB of the weakly bound 6Li+232Th system, it implies that a relationship may exist in between the reaction threshold and break threshold. Therefore, the systematic relationship between the reaction threshold and the breakup threshold demands further investigation. This highlights the influence of breakup on the reaction cross section and can yield valuable insights for reactions involving weakly bound nuclei.